2005
DOI: 10.1016/j.otohns.2004.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcomes for second primary head and neck cancer: A matched analysis

Abstract: B-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In a study of the survival time of MPMN, Wang et al (2005) compared second primary SCLC to first primary SCLC and found no significant differences in efficacy and median survival time. Bhattacharyya and Nayak (2005) found that second primary cancer survival rates were higher than those of the first primary tumors of head and neck cancer, but the results were not statistically significant. In addition, the survival rate of second primary cancer was associated with lesion sites.…”
Section: Discussionmentioning
confidence: 83%
“…In a study of the survival time of MPMN, Wang et al (2005) compared second primary SCLC to first primary SCLC and found no significant differences in efficacy and median survival time. Bhattacharyya and Nayak (2005) found that second primary cancer survival rates were higher than those of the first primary tumors of head and neck cancer, but the results were not statistically significant. In addition, the survival rate of second primary cancer was associated with lesion sites.…”
Section: Discussionmentioning
confidence: 83%
“…Hypopharyngeal cancer patients appeared to be at highest excess risk of solid tumor SPM development [17]. Depending on head and neck subsite, estimated five-year survival rates for HNSCC patients with a SPM ranged from 0–67%, compared to 36–46% for those without a SPM [1822]. The difference became more drastic at 10 years, when patients diagnosed with a SPM had a 19–22% survival rate, compared to 55% for those without a SPM.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The prognosis for patients who develop SPM is less favorable than the prognosis for patients with index SCCHN alone. 6,8,9 …”
Section: Introductionmentioning
confidence: 99%